Suntulip: New Tool to Simulate Solar Cells - Jasurbek Gulomov; Oussama Accouche; Bilel Neji; Jakhongir Ziyoitdinov (IEEE Access, 2023)
The article underscores the role of simulation in solar cell research, focusing on the newly-developed solar cell simulation program, Suntulip, which was written in C#. Given, the escalating significance of solar energy, optimizing solar cell efficiency and reducing costs has become vital for sustainability. Simulation has proven to be extremely efficient and cost-effective method compared to experimental and theoretical approaches. The introduction of Suntulip addresses the lack of a simulation library in C# and its potential contribution to solar cell research. Notably, the program’s reliability is substantiated through optical simulations and a comparison with Wafer Ray Tracer, demonstrating accurate and consistent results. The article emphasizes Suntulip’s user-friendly interface and versatile capabilities in calculating reflection, transmission, and absorption coefficients, hence providing valuable insights into solar cell behavior. As Suntulip continues to demonstrate its accuracy, it holds promises in advancing solar cell technology and facilitating sustainable energy solutions.